Methodical direction of instrumental and performance preparation of a future music teacher - Tsyutyupa, N.I. (Pedagogy of Higher and Secondary Education, 2006)
In clause the feature methodical preparation of the students in a rate "Technique of training to game on a piano" are opened, the ways of formation of knowledge and skills are determined which promote knowledge, and creation of musical images, and also their adequate reflection.